2011
DOI: 10.1093/europace/eur389
|View full text |Cite
|
Sign up to set email alerts
|

Frequent premature atrial complexes predict new occurrence of atrial fibrillation and adverse cardiovascular events

Abstract: Frequent PACs predict new AF and adverse cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 33 publications
7
112
2
Order By: Relevance
“…A hospital-based cohort study showed that patients with >100 APC/day had higher incident AF. 48 Findings of arrhythmia at a medical examination are thus extremely important for the prediction of AF.…”
Section: Resultsmentioning
confidence: 99%
“…A hospital-based cohort study showed that patients with >100 APC/day had higher incident AF. 48 Findings of arrhythmia at a medical examination are thus extremely important for the prediction of AF.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18]20,22,23 Several recent studies indicate that Holterdetected frequent APBs, or APBs present on a routine 12-lead ECG, 19,20 are an independent risk factor for stroke or death; previous studies used different thresholds for defining frequent APBs during a 24-hour recording (>100, 16 >218, 14 >228 APBs, 18 or >720 APBs or episodes of atrial tachycardia >20 beats long 15 ). In our study, we found that nearly 50% patients with cryptogenic stroke had an APB frequency >720/24 h, which is potentially clinically important based on the above literature.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16]26,27 For example, PACs have previously been associated with an increased risk of incident AF in population based cohort studies. [13][14][15][16] Furthermore, Inoue et al found that ablation of PACs in addition to pulmonary vein isolation was associated with a high probability of recurrence-free survival among patients with persistent AF undergoing catheter ablation, suggesting that these electric triggers may play an important role in AF initiation. 27 In addition, subclinical atrial arrhythmias like PACs or pacemaker-detected atrial tachyarrhythmias have been related to an increased risk of stroke and death.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, subclinical atrial arrhythmias like PACs or pacemaker-detected atrial tachyarrhythmias have been related to an increased risk of stroke and death. [13][14][15][16][17][18] Taken together, although our study may not have immediate clinical implications, more data are urgently needed to better understand the significance of our findings that PACs are present in the great majority of individuals aged Ն50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation